2019
DOI: 10.1088/1361-6528/ab1dcd
|View full text |Cite
|
Sign up to set email alerts
|

New coupling mechanism of titanium nitride nanosphere dimers at short separation distances

Abstract: The coupled localized plasmon modes generated by a metal plasmonic nanoparticle (NP) dimer induces a stronger plasmon enhanced electromagnetic field as well as a stronger optical response compared to that of a single NP. Owing to the small Drude damping factor, however, the absorption bandwidth of noble metallic NPs is insufficiently broad. Herein, the near-field wide band coupling absorption for 25 nm diameter TiN nanospheres is investigated in a homo-dimer arrangement for various separation distances using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Using the data analysis function of the Origin software can be deconvolved into the corresponding lorentz curve. Therefore, using the Lorentzian curve deconvolution method [8,44], the plasmonic modes of the Cu 2−x S@Au dimer were calculated from absorption spectra for gap = 2 nm, t = 2, 5, 10 nm, and t = 5 nm, gap = 2, 3, 15 nm, as shown in figures 5 and 6, respectively. Each peak deconvoluted from the curve in this way signifies a corresponding plasmonic mode, and three peaks (Peaks 1, 2, 3) were identified in figures 5 and 6.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the data analysis function of the Origin software can be deconvolved into the corresponding lorentz curve. Therefore, using the Lorentzian curve deconvolution method [8,44], the plasmonic modes of the Cu 2−x S@Au dimer were calculated from absorption spectra for gap = 2 nm, t = 2, 5, 10 nm, and t = 5 nm, gap = 2, 3, 15 nm, as shown in figures 5 and 6, respectively. Each peak deconvoluted from the curve in this way signifies a corresponding plasmonic mode, and three peaks (Peaks 1, 2, 3) were identified in figures 5 and 6.…”
Section: Resultsmentioning
confidence: 99%
“…The radius (r = t + r 1 ) satisfies the requirements of the Rayleigh approximation, where t and r 1 represent the shell thickness and core radius, respectively, and gap represents the interparticle edge-to-edge separation distance. It has recently been reported that the coupling behavior of NPs is closely related to the polarization direction of the incident light [8,[31][32][33]. Thus, herein, we only calculate the absorption spectra for the parallel polarization direction by the Finite Element Method (FEM) in COMSOL Multiphysics software 5.2 a (installed on a Quad Intel Xeon CPU, 256 GB RAM workstation), with which the absorption is most sensitive to different separation gaps (figure 1(b)).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among plasmonic ceramics, carbides and nitrides have larger damping factors in comparison to Au NPs. This makes them suitable candidates for application as NPs aiming to attain broadband absorption …”
Section: Introductionmentioning
confidence: 99%
“…This makes them suitable candidates for application as NPs aiming to attain broadband absorption. 56 Additionally, these NPs hold considerable potential for applications in the field of biology due to their biocompatibility, as evidenced by their localized surface plasmon resonance (LSPR) falling within the biological transparency range of 700 to 1000 nm. Moreover, their substantial absorption cross-section at the plasmon resonance makes them promising for utilization in plasmonic heating applications.…”
Section: Introductionmentioning
confidence: 99%